Maximum voltage angle optimization of uninterruptible power supply on three-level transformer-less photovoltaic inverter - Muhammad Irwanto (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/